Grain supplementation of calves as an alternative beef production system to pasture-finished steers in Chilean Patagonia: meat quality and fatty acid composition. Issue 1 (24th December 2019) - Sales, Francisco; Bravo-Lamas, Leire; Realini, Carolina E; Lira, Raúl; Aldai, Noelia; Morales, Rodrigo
Abstract: Beef production in Chilean Patagonia is based on steer finishing on pastures with low nutritive value. Grain supplementation for finishing calves on pasture arises as an attractive alternative to shorten the finishing phase and improve the production efficiency of the traditional system. The aim of this study was to compare meat quality and fatty acid (FA) composition of beef from steers and calves. Forty Angus cross steers were raised on pasture and slaughtered at 18 to 20 mo of age (448 ± 31.7 kg body weight). An additional group of 10 calves from similar genetics was weaned at 9 mo of age (303 ± 8.0 kg) and subsequently supplemented with 2.5 kg corn plus 1.0 kg commercial concentrate daily while on pasture during 47 d, until they reached slaughter weight (316 ± 13.9 kg). All animals were slaughtered on the same day and the Longissimus thoracis muscle was removed from each carcass for meat quality and FA profile analysis. Hot carcass weight from calves was lighter than steers (174 ± 7.9 vs. 224 ± 17.5 kg, P  ≤ 0.001). Meat from calves was lighter (higher L *) and less red (lower a *). In addition, meat from calves showed lower level of yellow pigments in subcutaneous fat (lower b *) compared with meat from steers ( P  ≤ 0.001). Meat from calves was more tender than meat from steers ( P  ≤ 0.05), although both shear force values were low and within recommendations for high consumer acceptability. Meat from both production systems showed fat content and FA profiles within dietary recommendations for a healthy diet. However, meat from calves was leaner (1.10 ± 0.29 vs. 2.00 ± 0.72% fat, P  ≤ 0.001). Meat from calves showed lower percentages of saturated ( P  ≤ 0.05) and monounsaturated ( P  ≤ 0.001) FAs and higher percentages of polyunsaturated and n-3 ( P  ≤ 0.001) FAs and conjugated linoleic acid (total and 9 c, 11 t -18:2 isomer, P  ≤ 0.001) than meat from steers. Grain supplementation of calves on pasture can reduce the finishing period by 8 to 10 mo at the expense of lighter carcasses with similar or improved meat quality characteristics compared with the traditional finishing of steers on pasture. Implementation of the alternative production system will depend mainly on feed costs and target carcass weights for specific markets.